Antagonistic effects of fertilizer on photochemical efficiency of Hibiscus cannabinus L. (kenaf) planted on beach ridges interspersed with swales soil - Yusoff, Mohd Hazimy; Abdul Hamid, Hazandy; Abdu, Arifin; Senin, Abdul Latib; Wan Abdul Rahman, Wan Mohd Nazri (Science Publications, 2011)
Problem statement: Hibiscus cannabinus L. or Kenaf is a highly productive, warmseasonal C3 annual crop and is one of the potential candidates to substitute kenaf fiber as raw product for pulp and paper production. It survives well on less fertile soils including those of Beach Ridges Interspersed with Swales (BRIS) soil. Approach: The objective of this study was to determine the effect of fertilizer on photochemical efficiency of H. cannabinus L. planted on BRIS soil using chlorophyll fluorescence technique. NPK with the ratio of 12:12:36 + 2MgO + TE (Trace-elements are mineral substances that act as an essential nutrients at a very low concentration) and the micronutrient of the trace elements compositions are Boron, Copper, Iron, Manganese, Molybdenum and Zinc were used for fertilizer treatment. Three levels of fertilizer treatments were applied in three plots; high (1960 kg plot-1), medium (1260 kg plot-1) and low (700 kg plot-1) respectively each plot comprising 106, 000 plants and were planted in 20 lines. Photochemical efficiency in terms of Fv/Fm ratio was determined under water deficit condition, fertilizer toxicity and interaction of both factors. Results: Contrasting trends for photochemical parameters were observed between different fertilizer levels where antagonistic effects were found between the three fertilizer treatments. The mean values ranged for minimal fluorescence (Fo) were from 256.27-273.06, maximal fluorescence (Fm) were from 970-1110.5, variable fluorescence (Fv) were from 705-854.23 and the ratio of Fv/Fm (photochemical efficiency) were from 0.72-0.77, respectively. Hitherto, for stress level, percentage for the low fertilizer level was 23.5% as compared to medium with 26.8 and 27.6% for high fertilizer level. Conclusion: The present study revealed that an appropriate amount of fertilizer is required to maximize the yield production cost effectively.